Implementation of Inclusive Education in an Educational Institution in Valledupar through Mathematics and Language - Garcia, Sheyla Salome Rodriguez; Oliveros, Martha Luz Gutierrez; Maestre, Elimeth Lilly Garcia; Ponton, Cesar Alfonso Manjarrez; Suarez, Denilson Johao Jimenez; Ramirez, Jhon Mateo Saurith (Journal of Posthumanism, 2024)
This article is part of a larger study which aimed to analyze the process of inclusive education in mathematics and language classes at the José Eugenio Martínez Technical Educational Institution, in the city of Valledupar - Cesar. The methodology used was qualitative and participatory, using tools such as interviews, focus groups, participant observation and documentary review, to collect data since teachers, students, parents and administrative staff and thus understand the experiences related to inclusive education in said Educational Institution, the investigated population was made up of students with some type of disability. mostly, visual and hearing disabilities who participate in math and language classes. The proposal concludes with the commitment to present detailed results supported by concrete examples, and specific recommendations will be offered to improve the implementation of inclusive education, focusing particularly on the teaching-learning process of blind and deaf students; In addition, it was evident that this approach requires a social and cultural conception of pedagogy in the two areas of knowledge.